Metabolic and Homeostatic Changes in Seizures and Acquired Epilepsy—Mitochondria, Calcium Dynamics and Reactive Oxygen Species - Stjepana Kovac (International Journal of Molecular Sciences, 2017)
Acquired epilepsies can arise as a consequence of brain injury and result in unprovoked seizures that emerge after a latent period of epileptogenesis. These epilepsies pose a major challenge to clinicians as they are present in the majority of patients seen in a common outpatient epilepsy clinic and are prone to pharmacoresistance, highlighting an unmet need for new treatment strategies. Metabolic and homeostatic changes are closely linked to seizures and epilepsy, although, surprisingly, no potential treatment targets to date have been translated into clinical practice. We summarize here the current knowledge about metabolic and homeostatic changes in seizures and acquired epilepsy, maintaining a particular focus on mitochondria, calcium dynamics, reactive oxygen species and key regulators of cellular metabolism such as the Nrf2 pathway. Finally, we highlight research gaps that will need to be addressed in the future which may help to translate these findings into clinical practice.